Oxidative DNA damage in osteoarthritic porcine articular cartilage - Chen, Antonia F. (2008)
PURPOSE: Osteoarthritis (OA) is associated with increased levels of reactive oxygen species. This study investigated if increased oxidative DNA damage accumulates in OA articular cartilage compared with non-OA articular cartilage from pigs with spontaneous OA. Additionally, the ability of nitric oxide (NO) or peroxynitrite (ONOO(-)) induced DNA damage in non-OA chondrocytes to undergo endogenous repair was investigated. METHODS: Porcine femoral condyles were graded for the stage of OA, macroscopically by the Collins Scale, and histologically by the modified Mankin Grade. Levels of DNA damage were determined in non-OA and OA cartilage, using the comet assay. For calibration, DNA damage was measured by exposing non-OA chondrocytes to 0-12 Gray of x-ray irradiation. Non-OA articular chondrocytes were treated with 0-500 μM of NO donors (NOC-18 or SIN-1), and DNA damage assessed after treatment and 5 days recovery. RESULTS: A significant increase (p<0.01) in oxidative DNA damage occurred in OA chondrocytes in joints with Mankin Grades 3 or greater, compared to non-OA chondrocytes. The percentage of nuclei containing DNA damage increased significantly (p<0.001) from early to late grades of OA. An increase of approximately 0.65-1.7 breaks/1000kB of DNA occurred in OA, compared to non-OA nuclei. NOC-18 or SIN-1 caused significant DNA damage (p<0.001) in non-OA chondrocytes that did not undergo full endogenous repair after 5 days (p<0.05). CONCLUSION: Our data suggest significant levels of oxidative DNA damage occur in OA chondrocytes that accumulates with OA progression. Additionally, DNA damage induced by NO and ONOO(-) in non-OA chondrocytes does not undergo full endogenous repair.